Constitutionalism in the Viewpoint of Akhond Khorasani,Leader of the Iranian Constitutional Revolution (Global Journal of Human-Social Science, 2011)
Despite the constitutional revolution of Iran being one of the most important social movements in Iranian history and it was then that modern concepts entered the Iranian political social literature there has been few efforts made to understand and grasp these concepts This article intends to evaluate the viewpoint of the religious leader of constitutionalist Akhond Khorasani in relation to the modern concepts of constitutionalism I e lawful government The dominant political system that presided the constitutional revolution was absolute monarchy and their always was a sole individual who ruled Iran in a complete dictatorial fashion as its king The constitutional movement demanded for the first time a parliamentary or constitutionalist government In this article all the primary documents and sources such as announcements letters telegraphs fatwas and answers to questions through which Akhond Khorasani expressed his views vis- -vis the concepts constitutionalism are analyzed by means of the hidden content analysis methodology and by using the viewpoints of Habermas the German sociologist who has respected views regarding the theory of modernity In the political culture of Iran which is completely mixed with religion there still is a challenge for understanding modern concepts and therefore making sense of the views held by the leader of the Iranian constitutional revolution who looked at political issues through the lens of religion can be a first step in better understanding how religion plays out its role in the Iranian political culture
Keywords: Constitutionalism; Iranian history; Modernity theory; Religion; Politic